2017
DOI: 10.1242/jcs.197236
|View full text |Cite
|
Sign up to set email alerts
|

Independent mechanisms recruit the cohesin loader protein NIPBL to sites of DNA damage

Abstract: NIPBL is required to load the cohesin complex on to DNA. While the canonical role of cohesin is to couple replicated sister chromatids together until the onset of mitosis, it also promotes tolerance to DNA damage. Here, we show that NIPBL is recruited to DNA damage throughout the cell cycle via independent mechanisms, influenced by type of damage. First, the heterochromatin protein HP1γ (also known as CBX3) recruits NIPBL to DNA double-strand breaks (DSBs) through the corresponding HP1-binding motif within the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
33
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 50 publications
(78 reference statements)
5
33
0
1
Order By: Relevance
“…Molecular analyses of these cells indicated that NIPBLΔN is still able to bind chromatin and to mediate cohesin loading onto DNA despite the absence of MAU2. This notion is in line with recent findings stating that a mutant NIPBL construct that is incapable to interact with MAU2 is still able to stimulate the ATPase activity of the cohesin complex and to mediate DNA repair 37,38 . Similarly, Murayama and Uhlmann formerly reported that in vitro NIPBL alone displayed DNA binding properties indistinguishable from that of the kollerin complex and was able to mediate cohesin loading onto chromatin 2 .…”
Section: Discussionsupporting
confidence: 90%
“…Molecular analyses of these cells indicated that NIPBLΔN is still able to bind chromatin and to mediate cohesin loading onto DNA despite the absence of MAU2. This notion is in line with recent findings stating that a mutant NIPBL construct that is incapable to interact with MAU2 is still able to stimulate the ATPase activity of the cohesin complex and to mediate DNA repair 37,38 . Similarly, Murayama and Uhlmann formerly reported that in vitro NIPBL alone displayed DNA binding properties indistinguishable from that of the kollerin complex and was able to mediate cohesin loading onto chromatin 2 .…”
Section: Discussionsupporting
confidence: 90%
“…Other possible chromatin receptors for the cohesin loader are the human mediator complex, that is found at active promoters (Kagey et al 2010 ), the yeast kinetochore complex Ctf19 (Hinshaw et al 2017 ) and the heterochromatin protein HP1γ at sites of DNA damage (Bot et al 2017 ). Whether centromeric chromatin and heterochromatin hold distinct qualities that make them permissive for cohesin loading without assistance of chromatin remodellers, or whether chromatin remodellers are required cofactors for cohesin loading at these sites, remains to be determined.…”
Section: Requirements For Cohesin Loading Onto Chromatinmentioning
confidence: 99%
“…Of interest, NIPBL, recently found to be necessary for loop extrusion 24,25 , is recruited at laser induced damages in a manner that depends on DDR kinases 31 . We therefore assessed the consequences of pharmaceutical inhibition of the ATM kinase activity on the interaction frequency post-DSB.…”
unclassified